Dosa Karena Lidah (Yakobus 3:1-12) - Delfiana Tena; Abad Jaya Zega (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Sin of the tongue is sin that comes out of the mouth and is expressed through words that are unpleasant for other people to hear. The tongue is a small part of the body, but it can also detect a person's physical condition through spoken words like those above. This means that someone can detect whether someone is mature in God or not, all of which can be known through the words they say. With the tongue, humans praise God's name, but with the same tongue, humans curse humans who were created in the image and likeness of Allah. From the same tongue come blessings and curses (Jas. 3:1-12). Here James emphasizes,